Near-canopy horizontal concentration heterogeneity of semivolatile oxygenated organic compounds and implications for 2-methyltetrols primary emissions. Issue 1 (21st December 2020) - Ye, Jianhuai; Batista, Carla E.; Guimarães, Patricia C.; Ribeiro, Igor O.; Vidoudez, Charles; Barbosa, Rafael G.; Oliveira, Rafael L.; Ma, Yongjing; Jardine, Kolby J.; Surratt, Jason D.; Guenther, Alex B.; Souza, Rodrigo A. F.; et al.
Abstract : This study calls attention to the primary emissions of semivolatile oxygenated organic compounds (SV-OVOCs) and demonstrates how mapping out the near-canopy concentration can effectively isolate atmospheric SV-OVOC production from direct emissions. Abstract : Semivolatile oxygenated organic compounds (SV-OVOCs) are important atmospheric species, in particular for the production and chemistry of atmospheric particulate matter and related impacts on air quality and climate. In this study, SV-OVOCs were collected in the horizontal plane of the roughness layer over the tropical forest in the central Amazon during the wet season of 2018. A sampler mounted to a copter-type, hovering unmanned aerial vehicle was used. Underlying the collection region, a plateau forest transitioned into a slope forest across several hundred meters. The concentrations of pinonic and pinic acids, which are monoterpene oxidation products, had no statistical difference over the two forests. By comparison, across the study period, differences in the concentration of 2-methyltetrols, which are products of isoprene oxidation, ranged from −70% to +480% over the two forests. The chemical lifetime of 2-methyltetrols in the atmosphere is sufficiently long that heterogeneity in the isoprene emission rate from the two forests followed by atmospheric oxidation does not explain the concentration heterogeneity of 2-methyltetrols. Standing waves and local meteorology also cannot account for the heterogeneity. Of the possibilities considered, the most plausible explanation is the direct emission from the forest of 2-methyltetrols produced through biological processes within the plants. Under this explanation, the rate of direct SV-OVOC emissions should be modulated by forest type and related environmental stressors. Direct emissions of SV-OVOCs should be more broadly considered for constraining and improving models of atmospheric composition, transport, and chemistry over tropical forests.